The fermented man : a year on the front lines of a food revolution - Dellinger, Derek (The Overlook Press, 2016)
"A writer, brewer and fermentation enthusiast chronicles his year spent drinking and eating only products that had been created by microbes, becoming the living embodiment of the cultural and nutritional power of fermentation,"--NoveList.